Building of small shelter using steel cold-formed lipped channel : shelter design and members behaviour - Quek, Jia Wei. (2010)
In the event of natural disasters, buildings are generally destroyed leaving population homeless. Housing would be a problem for many in the immediate years after the diaster. This project aims to design a rapid deployable shelter for the refugees using cold-formed lipped channel steel and self-tapping screws as the main materials.